Kept from all contagion : germ theory, disease, and the dilemma of human contact in late nineteenth-century literature - Nixon, Kari (Albany : State University of New York Press, 2020)
"Kept from All Contagion explores the surprising social effects of germ theory in the late nineteenth-century. Connecting groups of others rarely studied in tandem by highlighting their shared interest in changing interpersonal relationships in the wake of germ theory, this book takes a surprising and refreshing stance on studies in medicine and literature. Each chapter focuses on a different disease, discussing the different social policies or dilemmas that arose from new understandings in the 1860s-90s that these diseases were contagious. The chapters pair these sociohistorical considerations with robust literary analyses that assess the ways authors as diverse as Thomas Hardy, Henrik Ibsen, and Mary Elizabeth Braddon, among others, grappled with these ideas and their various impacts upon different human relationships -- marital, filial, and social. Through the trifocal structure of each chapter (microbial, relational, and socio-political), the book excavates previously overlooked connections between such literary texts that insist upon the life-giving importance of community engagement -- the very thing that seemed threatening in the wake of germ theory's revelations. Germ theory seemed to promote self-protection via isolation; the authors covered in Kept from All Contagion resist such tacit biopolitical implications and instead, as Nixon shows, repeatedly demonstrate vitalizing interpersonal interactions in spite of -- and often because of -- their contamination with disease, thus completely upending both the ways Victorians and present-day literary scholars have tended to portray and interpret purity"--
Introduction: "The germ theory again" : disease, ideology, and the possibilities of biotic life in the world of antibiotic purity -- Keep bleeding : plague, vaccination debates, and the necessity of leaky boundaries in Defoe's Journal of the plague year and Shelley's The last man -- "A speculative idea" : childbed fever, early germ theory debates, and (en)gendered speculation in Henry James's Washington Square -- Separation and suffocation : tuberculosis, etiological uncertainty, and female friendship in women's fiction -- Tainted love : venereal disease, morality, and the contagious disease acts in Ibsen's Ghosts and Hardy's The woodlanders and Jude the obscure -- Humanity's waste : typhoid fever, the failure of isolation, and the development of probiotics in three late-century works -- Conclusion: Shuffling within our mortal coil : concluding remarks.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Communicable diseases in literature; Germ theory of disease -- History -- 19th century; Literature and medicine -- History -- 19th century; Medicine in literature; Literature, Modern -- 19th century; Medicine in Literature -- history; Communicable Diseases -- history; Germ Theory of Disease -- history; Socioeconomic Factors -- history; Health Knowledge, Attitudes, Practice; History, 19th Century; Medicine in Literature; Literature, Modern; Maladies infectieuses dans la littérature.; Bactéries -- Cause de maladies -- Histoire -- 19e siècle.; Littérature et médecine -- Histoire -- 19e siècle.; Médecine dans la littérature.; Littérature -- 19e siècle.; Médecine -- Histoire -- 19e siècle.; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Communicable diseases in literature; Germ theory of disease; Literature and medicine; Literature, Modern; Medicine in literature; Communicable diseases in literature; Germ theory of disease -- History -- 19th century; Literature and medicine -- History -- 19th century; Medicine in literature; Literature, Modern -- 19th century; Maladies infectieuses -- Transmission -- Dans la littérature.; Littérature et médecine -- 19e siècle.; 1800-1899; History; Literary criticism; Critiques littéraires.